Morphological and physiological changes in Saccharomyces cerevisiae by oxidative stress from hyperbaric air - Belo, Isabel (2005)
Increase in air or oxygen pressure in microbial cell cultures can cause oxidative stress and consequently affect cell physiology and morphology. The behaviour of Saccharomyces cerevisiae grown under hyperbaric atmospheres of air and pure oxygen was studied. A limit of 1.0 MPa for the air pressure increase (i.e. 0.21 MPa of oxygen partial pressure) in a fed-batch culture of S. cerevisiae was established. Values of 1.5 MPa air pressure and 0.32 MPa pure oxygen pressure strongly inhibited the metabolic activity and the viability of the cells. Also, morphological changes were observed, especially cell-size distribution and the genealogical age profile. Pressure caused cell compression and an increase in number of aged cells. These effects were attributed to oxygen toxicity since similar results were obtained using air or oxygen, if oxygen partial pressure was equal to or higher than 0.32 MPa. The activity of the antioxidant enzymes, catalase and superoxide dismutase (SOD) (cytosolic and mitochondrial isoformes) indicated that the enzymes have different roles in oxidative stress cell protection, depending on other factors that affect the cell physiological state.